2017
DOI: 10.1093/eurheartj/ehx512
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical outcomes of state-of-the-art percutaneous coronary revascularization in patients with de novo three vessel disease: 1-year results of the SYNTAX II study

Abstract: AimsTo investigate if recent technical and procedural developments in percutaneous coronary intervention (PCI) significantly influence outcomes in appropriately selected patients with three-vessel (3VD) coronary artery disease.Methods and resultsThe SYNTAX II study is a multicenter, all-comers, open-label, single arm study that investigated the impact of a contemporary PCI strategy on clinical outcomes in patients with 3VD in 22 centres from four European countries. The SYNTAX-II strategy includes: heart team … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 270 publications
(165 citation statements)
references
References 30 publications
5
135
0
17
Order By: Relevance
“…18 In this trial, 17 The SYNTAX II study (Synergy between Percutaneous Coronary Intervention with TAXUS and Cardiac Surgery), a single-arm, prospective study in patients with multivessel disease incorporating a management strategy including combined iwFR/FFR assessment of stenosis severity in addition to intravascular ultrasound (IVUS)-guided stent implantation and guideline-directed medical therapy, showed encouraging outcomes compared with a historical cohort enrolled in the SYNTAX trial. 34 Randomized trials comparing iwFR-guided revascularization with angiography-guided revascularization or medical therapy are not available. iwFR has not been extensively validated for patients with LMS stenosis.…”
Section: Fractional Flow Reserve-guided Management Vs Medical Therapmentioning
confidence: 99%
“…18 In this trial, 17 The SYNTAX II study (Synergy between Percutaneous Coronary Intervention with TAXUS and Cardiac Surgery), a single-arm, prospective study in patients with multivessel disease incorporating a management strategy including combined iwFR/FFR assessment of stenosis severity in addition to intravascular ultrasound (IVUS)-guided stent implantation and guideline-directed medical therapy, showed encouraging outcomes compared with a historical cohort enrolled in the SYNTAX trial. 34 Randomized trials comparing iwFR-guided revascularization with angiography-guided revascularization or medical therapy are not available. iwFR has not been extensively validated for patients with LMS stenosis.…”
Section: Fractional Flow Reserve-guided Management Vs Medical Therapmentioning
confidence: 99%
“…1 Characteristics of the SYNTAX II strategy that captures all components of today's 'best of PCI practice' are summarized in Figure 2. Following this approach systematically, the authors demonstrated major adverse cardiac and cerebrovascular events (MACCE) at 1 year to be much improved with respect to a matched historical PCI cohort from the SYNTAX I trial (10.6% vs. 17.4%; P = 0.006).…”
Section: Myocardial Revascularization Percutaneous Coronary Interventmentioning
confidence: 99%
“…Because these results outperform PCI results obtained in the earlier SYNTAX I trial, the hypothesis was generated that a new randomized study of modern best PCI practice in patients with three-vessel disease might show non-inferiority vs. coronary artery bypass grafting (CABG). 1 Glimpsing to the future, the feasibility and technical success of robotically-assisted PCI for complex coronary lesions were investigated in 334 procedures from 315 patients included in the Complex Robotically Assisted Percutaneous Coronary Intervention (CORA-PCI) study. 2 In 108 procedures of robotically-assisted PCI, technical success was 91.7% and clinical success was 99.…”
Section: Myocardial Revascularization Percutaneous Coronary Interventmentioning
confidence: 99%
See 1 more Smart Citation
“…Jednym z najważniejszych wydarzeń pierwszego dnia kongresu była prezentacja (w ramach sesji "Hot Line-Late--Breaking Science in PCI") wyników badania SYNTAX II [1], dotyczącego porównania wyników rewaskularyzacji wieńcowej metodą chirurgiczną (CABG, coronary artery bypass grafting) i metodami przezskórnymi (PCI, percutaneous coronary intervention) z użyciem współczesnych stentów uwalniających leki (DES, drug-eluting stent). O ile we wcześniejszym badaniu SYNTAX I porównywano wyniki leczenia techniką CABG w chorobie wielonaczyniowej ze standardowym zabiegiem angioplastyki, o tyle w obecnym badaniu uwzględniono ogromny postęp w zakresie oceny istotności hemodynamicznej zmian w łożysku wieńcowym.…”
unclassified